Introduction of Cosmid pHU 52 Into HUP Azospirillum SP. BSs 8 BY Transconjugation and Transformation - Juanita C Mamaril; Elizabeth P Ko; Lorele C. Trinidad (Universitas Gadjah Mada, 1988)
Introduction of Cosmid pHU 52 Into HUP Azospirillum SP. BSs 8 BY Transconjugation and Transformation